Reports investigations into the industrial conditions in certain depressed areas of I. West Cumberland and Haltwhistle, II. Durham and Tyneside, III. South Wales and Monmourshire, IV. Scotland. Presented by the Minister of Labour to Parliament [...], November, 1934 (His Majesty's Stationery Office, 1934)
Ministry of Labour.